The barriers to acceptance of statistical methods of quality control in the Macedonian manufacturing industry - Bucevska, Vesna (International Statistical Instititute (ISI), 2001)
This paper reveals that industry in the Republic of Macedonia makes surprisingly little use of statistical methods of quality control (SQC) and describes the reasons for its low usage. In summary, the major barrier preventing companies from introducing SQC is lack of knowledge. Whilst this was often not the first reason given, much circumstantial evidence from questionnaires and direct evidence from interviews suggest that decisions are often taken on the basis of very little or no knowledge. Clearly, there is an urgent need to increase awareness and knowledge of SQC
Keywords: statistical quality control, statistical process control, manufacturing, Macedonia